2023
DOI: 10.1111/mec.17048
|View full text |Cite
|
Sign up to set email alerts
|

Sex chromosome heteromorphism and the Fast‐X effect in poeciliids

Abstract: Owing to their unusual inheritance pattern and hemizygosity in males, X chromosomes display many distinct evolutionary properties compared to the rest of the genome (Charlesworth et al., 1987;Vicoso & Charlesworth, 2006). The strength of selection and genetic drift, as well as the role of dominance and effective population size, are expected to differ between sex chromosomes and autosomes (Kirkpatrick & Hall, 2004;Mank et al., 2010;Meisel & Connallon, 2013). Comparing differences in the evolution of sexlinked … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…Various models have been proposed for the evolutionary history of sex chromosomes in the clade of Poeciliids encompassing P. reticulata , P. wingei , P. picta , and P. parae ( Darolti et al 2019 ; Charlesworth et al 2021a ; Fong et al 2023 ). However, all available evidence suggests that the sex chromosome arose in the ancestor to P. reticulata , P. wingei , P. picta , and P. parae , ∼20 mya ( Metzger et al 2021 ; Sandkam et al 2021 ; Darolti et al 2023 ; Fong et al 2023 ). Based on this model, extensive Y Chromosome degradation and dosage compensation evolved in the common ancestor of P. picta and P. parae after the split from P. reticulata and P. wingei .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various models have been proposed for the evolutionary history of sex chromosomes in the clade of Poeciliids encompassing P. reticulata , P. wingei , P. picta , and P. parae ( Darolti et al 2019 ; Charlesworth et al 2021a ; Fong et al 2023 ). However, all available evidence suggests that the sex chromosome arose in the ancestor to P. reticulata , P. wingei , P. picta , and P. parae , ∼20 mya ( Metzger et al 2021 ; Sandkam et al 2021 ; Darolti et al 2023 ; Fong et al 2023 ). Based on this model, extensive Y Chromosome degradation and dosage compensation evolved in the common ancestor of P. picta and P. parae after the split from P. reticulata and P. wingei .…”
Section: Discussionmentioning
confidence: 99%
“…1 A). Although several phylogenetic models have been suggested for the origin of the sex chromosomes and dosage compensation in these species ( Charlesworth et al 2021a ), comparative phylogenetic and genomic methods ( Metzger et al 2021 ; Darolti et al 2023 ; Fong et al 2023 ) suggest that the sex chromosomes diverged and complete dosage compensation evolved in a short interval between 14.8 and 18.5 mya ( Fig. 1 A; Metzger et al 2021 ).…”
mentioning
confidence: 99%
“…Similarly, in Sylvioidea songbirds, there is no difference in evolutionary rates between the neo-Z and autosomes (Leroy et al, 2021). Darolti et al (2023) further showed that while Faster-X correlates with hemizygosity in various species of poeciliid fishes, no evidence of increased drift or differences in divergence rates could be detected between diploid X chromosomes and their respective autosomes. Therefore, the broad relevance of the Slower-X effect in taxa with young sex-linked regions is still to be fully explored.…”
Section: Introductionmentioning
confidence: 95%